Lumbar Forces While Making a Bed With and Without an Instant Tuck™ Mat - Gluck, Dr. Adrian; Abdo, Dr. Armia; Al-Nakhli, Dr. Hani (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Conventional wisdom to avoid back pain while making your bed recommends not to lean across your bed to tuck in the sheets, and to keep your back straight and use Core Muscles. This is not practical or possible with any of the many different designs currently available. At present, there is no safe way to make your bed, which can significantly increase the risk of injury and create lifelong disabilities for both individuals and certain professional bedmakers such as house keepers, and caregivers. Objective: It was hypothesized that the use of an Instant Tuck™ Mat can significantly lower the Back-Compression Force (BCF) on the Lower Back and fall far below the risk threshold level stated by the NIOSH. The Instant Tuck™ Mat addresses this major health problem of back pain and injuries by eliminating the need to ever lift a mattress when making the bed. Method: A sample of 35 subjects performed the task of making a bed with a queen-sized mattress with and without the Instant Tuck™ Mat in a random order. BCF, the number of lifts to make the bed as well as the length of time for each lift, and the number of times each individual bent forward was measured during each trial. Results: There were significant differences for all the measured variables. Regarding the BCF, there was an approximately 85% reduction of pressure on the lower back when using the Instant Tuck™ Mat vs. not using it, which was a highly significant decrease (p<.001). Also, the number of times the mattress was lifted was lower by 12 times when using the Instant Tuck™ Mat vs. not using it (p<.001). Finally, the times each individual bent down was approximately 9 times less when using the Instant Tuck™ Mat vs. not using it (p<.001). Conclusion: BCF’s making a bed in its current form is by a wide margin out of compliance with NIOSH standards and as a result it poses a significant risk of injury especially for those who are required to perform this for their occupation, such as hotel housekeepers and hospital, nursing home, and in-home caregivers. Making a bed using the Instant Tuck™ Mat reduced the BCF’s by 85% and is in line with NIOSH standards. The Instant Tuck™ Mat has that it can make the repetitive act of making a bed safe and that it can significantly reduce the risk of injury based on NIOSH standards.